Imaging and clinical efficacy analysis of minimally invasive reduction and crossbar external fixation in the treatment of Sanders Ⅱ and Ⅲ calcaneal fractures - Wang, Jianchuan; Guan, Tianmin; Xue, Qiwen (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical efficacy of percutaneous minimally invasive reduction combined with crossbar external fixation in the treatment of Sanders type II and III calcaneal fractures.MethodsA retrospective analysis was performed on 65 patients with Sanders type II and III calcaneal fractures who were treated at Zhongshan Hospital affiliated with Dalian University between February 2019 and June 2021. Among them, 48 were males and 17 were females, with a mean age of 42.3 ± 10.2 years. There were 45 cases of Sanders type II fractures and 20 cases of type III fractures. Patients were divided into three groups based on the surgical methods: Group A (n = 25, minimally invasive reduction with crossbar external fixation), Group B (n = 21, minimally invasive locking plate fixation via the sinus tarsi approach), and Group C (n = 19, locking plate fixation via the lateral L-shaped incision). The following parameters were recorded and compared among the groups: preoperative waiting time, operative duration, intraoperative blood loss, incision length, and postoperative complications. Imaging parameters assessed included calcaneal length, width, height, Böhler angle, Gissane angle, and varus angle. Clinical outcomes were evaluated using the American Orthopedic Foot and Ankle Society (AOFAS) ankle-hindfoot score, Visual Analogue Scale (VAS), Short Form Health Survey (SF-36), and Maryland Foot and Ankle Score.ResultsBaseline characteristics showed no significant differences among the groups (P > 0.05). All patients were followed up for an average duration of 15.6 ± 1.2 months. Group A demonstrated significantly shorter preoperative waiting times, operative durations, lower intraoperative blood loss, and shorter incision lengths compared with groups B and C (P < 0.05). Furthermore, VAS scores 3 days postoperatively were significantly lower in group A compared to groups B and C (P < 0.05), whereas no significant difference was observed between groups B and C. The incidence of postoperative complications was significantly lower in groups A and B compared with group C (P < 0.05), with no significant difference observed between groups A and B. In addition, complications observed in the study included pinhole infections, cyanosis of the skin at the edge of the incision, nerve damage, and skin necrosis. Statistically, the complication rate was significantly lower in the group with the percutaneous minimally invasive approach than in the group with the traditional L-shaped approach. Imaging assessments at 2 weeks and 12 months postoperatively revealed no significant differences among the three groups in Böhler angle, Gissane angle, calcaneal varus angle, and calcaneal dimensions (P > 0.05). All imaging parameters significantly improved postoperatively within each group (P < 0.05). At the final follow-up, clinical outcomes (AOFAS, SF-36, Maryland scores) showed no significant differences among groups (P > 0.05).ConclusionThe Percutaneous minimally invasive reduction combined with crossbar external fixation provides effective fixation with minimal trauma, shorter hospital stays, and lower complication rates, representing a viable treatment strategy for Sanders type II and III calcaneal fractures.